Europejska współpraca administracyjna w Kodeksie postępowania administracyjnego – kolejne martwe przepisy? - Tuszyńska, Anna; Warzycki, Michał (Kwartalnik Prawa Publicznego, 2017)
This article deals with legal regulations relating to European administrative cooperation which was implemented to polish administrative proceedings on 1st June 2017. This text applies to the Division VIIIa titled “European administrative cooperation”, adopted to The Code of Administrative Proceedings. The authors of the treatise discuss the legal basis of European administrative cooperation in other countries of European Union and the reasons for incorporation new regulation to polish administrative proceedings. Authors of the article also resolve results of ReNEUAL Model Rules on EU Administrative Procedure project in the part referring to European administrative cooperation, which was the model for the Polish legislator. Authors also analyze the articles of The Code of Administrative Proceedings concerning European administrative cooperation and emphasize the interpretative problems which may occur in the law application process. In summary, authors discuss the reasons for which legal regulations concern European administrative cooperation may be used occasionally.